Control of cell proliferation in Arabidopsis thaliana by microRNA miR396 - Rodriguez Virasoro, Ramiro Esteban (2010)
Cell proliferation is an important determinant of plant form, but little is known about how developmental programs control cell division. Here, we describe the role of microRNA miR396 in the coordination of cell proliferation in Arabidopsis leaves. In leaf primordia, miR396 is expressed at low levels that steadily increase during organ development. We found that miR396 antagonizes the expression pattern of its targets, the GROWTH-REGULATING FACTOR (GRF) transcription factors. miR396 accumulates preferentially in the distal part of young developing leaves, restricting the expression of GRF2 to the proximal part of the organ. This, in turn, coincides with the activity of the cell proliferation marker CYCLINB1;1. We show that miR396 attenuates cell proliferation in developing leaves, through the repression of GRF activity and a decrease in the expression of cell cycle genes. We observed that the balance between miR396 and the GRFs controls the final number of cells in leaves. Furthermore, overexpression of miR396 in a mutant lacking GRF-INTERACTING FACTOR 1 severely compromises the shoot meristem. We found that miR396 is expressed at low levels throughout the meristem, overlapping with the expression of its target, GRF2. In addition, we show that miR396 can regulate cell proliferation and the size of the meristem. Arabidopsis plants with an increased activity of the transcription factor TCP4, which reduces cell proliferation in leaves, have higher miR396 and lower GRF levels. These results implicate miR396 as a significant module in the regulation of cell proliferation in plants.